2017
DOI: 10.1164/rccm.201701-0193oc
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eosinophils and Response to Maintenance Chronic Obstructive Pulmonary Disease Treatment. Data from the FLAME Trial

Abstract: Our prospective analyses indicate that indacaterol/glycopyrronium provides superior or similar benefits over salmeterol/fluticasone regardless of blood eosinophil levels in patients with COPD. Clinical trial registered with www.clinicaltrials.gov (NCT01782326).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 40 publications
7
133
1
3
Order By: Relevance
“…More than one‐third (39.1%) of our patients have a BEC greater than 200, which is lower than the 49.4% mentioned by Hastie et al, as well as the 63.7% of the patients by Disantoestefano . Using the 300 cells/µL cut‐off point, 22.1% are equal or greater, similar to that referred to by Watz or Roche, but lower than other populations where these values increase between 32.5% and 41.4% . The results are more similar with a cut‐off point of 400 cells/µL, as 11.2% of our patients equal or exceed this figure, similar to the 11% mentioned by Watz et al, or to the 14.4% in the study by Disantoestefano …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…More than one‐third (39.1%) of our patients have a BEC greater than 200, which is lower than the 49.4% mentioned by Hastie et al, as well as the 63.7% of the patients by Disantoestefano . Using the 300 cells/µL cut‐off point, 22.1% are equal or greater, similar to that referred to by Watz or Roche, but lower than other populations where these values increase between 32.5% and 41.4% . The results are more similar with a cut‐off point of 400 cells/µL, as 11.2% of our patients equal or exceed this figure, similar to the 11% mentioned by Watz et al, or to the 14.4% in the study by Disantoestefano …”
Section: Discussionsupporting
confidence: 74%
“…The criteria to define eosinophilia vary widely. In our case we have chosen cut‐off points for the BEC of 200, 300 or 400/µL, which are of habitual use in the literature and help to establish comparisons with other studies . But other authors use different cut‐off points.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies [155][156][157] except one 158 have demonstrated that high blood eosinophils could be valuable to predict an increase response in terms of reduction of exacerbation rate when treated with combination ICS/LABA. However, all these studies were secondary analyses or post hoc subgroup analyses.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…For example, it has been suggested that blood eosinophils could be useful clinically to predict COPD phenotype more likely to respond to ICS. [155][156][157][158][159] Another example is the bacterial colonization in some COPD patients that could contribute to the biological mechanisms of recurrent acute exacerbations. Under these circumstances, macrolides may reduce the risk for AECOPD although patients should be selected carefully considering the risk of bacterial resistance and side effects.…”
Section: Box 2 Preventing Acute Exacerbation In Stable Copdmentioning
confidence: 99%
“…Importantly, across all doses of ICS, fluticasone furoate and vilanterol reduced exacerbations by 29% compared with vilanterol alone in patients with eosinophil counts ≥2%, and by 10% in patients with eosinophil counts <2%. Analysis of data from the FLAME trial showed no significant reduction in exacerbation in indacaterol/gycopyrronium compared to salmeterol/fluticasone among patients with blood eosinophil levels of 150 to 300 cells/μL versus 300 cells/μL . In this study, we use the word “eosinophilia” to mean an elevated blood eosinophil count based on our defined cutoffs.…”
Section: Introductionmentioning
confidence: 99%